2006
DOI: 10.1063/1.2210788
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanocrystals with ensemble quantum yields exceeding 60%

Abstract: Silicon nanocrystals with diameters of less than 5nm show efficient photoluminescence at room temperature. For ensembles of silicon quantum dots, previous reports of photoluminescence quantum yields have usually been in the few percent range, and generally less than 30%. Here we report the plasma synthesis of silicon quantum dots and their subsequent wet-chemical surface passivation with organic ligands under strict exclusion of oxygen. Photoluminescence quantum yields exceeding 60% have been achieved at peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
418
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(438 citation statements)
references
References 27 publications
17
418
1
2
Order By: Relevance
“…This is about 2 % higher than observed for highly similar butyl-terminated SiNPs, [48] but still considerably smaller than the highest QY reported for SiNPs (60 %). [53] It has been suggested that a high oxidation grade of the SiNPs results in lower quantum yields, [54] however, such high degrees of oxidation are absent in this case as follows from IR and XPS data. The larger size (2.5 nm in this case) is therefore a more likely cause.…”
mentioning
confidence: 97%
“…This is about 2 % higher than observed for highly similar butyl-terminated SiNPs, [48] but still considerably smaller than the highest QY reported for SiNPs (60 %). [53] It has been suggested that a high oxidation grade of the SiNPs results in lower quantum yields, [54] however, such high degrees of oxidation are absent in this case as follows from IR and XPS data. The larger size (2.5 nm in this case) is therefore a more likely cause.…”
mentioning
confidence: 97%
“…Si nanocrystals are of intrinsic interest due to their potential to overcome the indirect character of the lowest-energy interband transition and to be useful in optoelectronic devices. [39][40][41] Recently, Si nanocrystals with structures based on high-pressure bulk phases have been proposed as candidates for photovoltaic applications as they display multi-exciton generation and high quantum efficiencies. 42 They are also found to transform under pressure between a variety of crystalline and amorphous structures that are still the subject of theoretical and experimental investigations in both the porous and colloidal forms.…”
Section: Introductionmentioning
confidence: 99%
“…The first is that the probability of inter band transition is much lower for bulk silicon. Usually the emission quantum yield of nanocrystals from confinement state is much lower compared with their direct bandgap counterparts [87,98], while some exceptions have been observed [99,100]. The second is that a lattice matched barrier layer used in heavy metal dots, is absent for most preparation methods.…”
Section: Quantum Confinement In the Case Of Siliconmentioning
confidence: 99%
“…Among the third approach which is combination of the previous two methods non-thermal plasma assisted approach has distincted itself as being a prominent method for fabrication [99,[125][126][127][128][129]. In principle, the plasma environment initiates the breaking down of silane precursors in the reaction chamber.…”
Section: Preparation and The Impacts Of Surface Chemistrymentioning
confidence: 99%